2014
DOI: 10.1177/0886260514532524
|View full text |Cite
|
Sign up to set email alerts
|

Informal Social Reactions to College Women’s Disclosure of Intimate Partner Violence

Abstract: This researchers assessed informal (e.g., friends, family) social reactions to college women's (N = 139) disclosure of intimate partner violence (IPV) within their current romantic relationships and associated psychological (i.e., posttraumatic stress symptoms [PTSS] and global psychological distress symptoms) and relational (i.e., intentions to leave the abusive relationship) variables. Women completed confidential surveys, which assessed current partner abuse, psychological and relational variables, and thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
69
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 38 publications
5
69
0
1
Order By: Relevance
“…One of these themes was social support, including access to or lack of access. Researchers highlight the role that available social support plays on the ability to leave an abusive relationship (Barnett 2001;Edwards et al 2015;Kim and Gray 2008;Koepsell et al 2006). Koepsell et al (2006) found that victims who sought social support, but did not receive it were less likely to leave an abusive relationship.…”
Section: External Factorsmentioning
confidence: 97%
See 1 more Smart Citation
“…One of these themes was social support, including access to or lack of access. Researchers highlight the role that available social support plays on the ability to leave an abusive relationship (Barnett 2001;Edwards et al 2015;Kim and Gray 2008;Koepsell et al 2006). Koepsell et al (2006) found that victims who sought social support, but did not receive it were less likely to leave an abusive relationship.…”
Section: External Factorsmentioning
confidence: 97%
“…Further, certain types of social support are more helpful than others. For example, there are three common reactions that people have when hearing of abuse (Edwards et al 2015): (1) positive or validating, (2) negative or blaming and disbelieving, and (3) leaving, specifically being encouraged to leave. Victims who received negative reactions, such as blaming or disbelieving, often experienced significantly more psychosocial distress, while those who received positive or supportive reactions frequently reported intention to leave and less distress.…”
Section: External Factorsmentioning
confidence: 99%
“…Immediate linkage to services is critical when the survivor is at risk of HIV transmission, pregnancy, or severe physical injury. However, disclosure can increase psychopathology symptoms, particularly when the response to disclosure is negative (Edwards, Dardis, Sylaska, & Gidycz, 2014; Roesler, 1994). Reactions to disclosure depend on factors such as community perceptions of SV and the relationship of the perpetrator to the survivor (Jewkes, Penn-Kekana, & Rose-Junius, 2005; Ullman & Filipas, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, survivors who disclose during childhood and receive a negative reaction (such as disbelief or blame) have higher levels of post-traumatic stress than do those who receive a positive reaction (Edwards et al, 2014; Roesler, 1994). Reactions to disclosure are influenced by SV characteristics as well as community perceptions of SV.…”
Section: Introductionmentioning
confidence: 99%
“…Extant literature suggests that societal stigmatization embedded in negative social reactions to IPV also may contribute to women’s depressive symptoms (Sylaska & Edwards, 2014; Edwards, Dardis, Sylaska, & Gidycz, 2015). Women who disclose experiences of IPV to informal support networks (e.g., family and friends) encounter both positive and negative reactions to their disclosure (Sylaska & Edwards, 2014; Trotter & Allen, 2009).…”
mentioning
confidence: 99%